The Impact of Online Slot Addiction on Social Behavior (Case of a teenager in Mataram City) - Wijaya, I Gde Khanara Arya; Mustari, Mohamad; Alqadri, Bagdawansyah; Sumardi, Lalu (UNDIKMA, 2025)
This study aims to analyze the impact of online slot addiction on the social behavior of adolescents in Mataram City. The research method used is a case study with a qualitative approach, involving in-depth interviews with adolescents addicted to online slots. The results indicate that online slot addiction negatively affects various aspects of adolescents' lives, including financial, social, and academic domains. Financially, adolescents tend to spend their pocket money uncontrollably and even borrow money from friends or family. Socially, this addiction isolates them from their social environment and reduces their involvement in community activities. Additionally, in the academic aspect, online slot addiction leads to declining academic performance due to a lack of focus and frequent absenteeism from school activities. The conclusion of this study confirms that online slot addiction is a detrimental phenomenon for adolescents' social development and requires attention from various parties, including families, schools, and the government. More intensive preventive and educational measures are necessary to mitigate the negative impact of this addiction and raise awareness among adolescents about the dangers of online gambling.